The Relationship of Socialization with The Formation of Kurdish Individual Personality - Saleem Patros Elias; Rozhgar Saadi Sabir (QALAAI ZANIST SCIENTIFIC JOURNAL, 2023)
The subject of the research (the relationship of socialization with the formation of the Kurdish individual personality) is a theoretical scientific research, with the aim of knowing and demonstrating the relationship with social institutions such as: family, school, religious institutions and media. Research objectives are: 1- Knowing the role of the family in socialization and its relations with the formation of the personality of the Kurdish individual. 2- Recognizing the role of the school in socialization and its relationship to the formation of the Kurdish individual's personality. 3- Familiarizing with the role of religious institutions in social upbringing and their relations to the formation of the Kurdish individual's personality. 4- Understand the role of the media tools in socialization and its relationship to the formation of the Kurdish individual's personality.